PENGARUH INTEGRASI APLIKASI MOBILE FITNESS TRACKER (STRAVA) TERHADAP MINAT DAN KEAKTIFAN SISWA SMK DALAM PEMBELAJARAN PJOK - Pasyahari; Husni Tamim; Prietia Eko Wardoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Physical fitness and physical activity levels among Indonesian adolescents remain concerning, while Physical Education (PJOK) at the vocational high school (SMK) level tends to be positioned as a secondary subject due to strong vocational orientation. This study aims to examine the effect of integrating the Strava mobile fitness tracker application on learning interest and physical activeness of students at SMK Negeri 3 Selong in PJOK learning. A quantitative approach with a quasi-experimental pretest-posttest control group design was employed, involving 60 students divided into an experimental group (n=30) using Strava in a structured manner for three to four weeks and a control group (n=30) following conventional PJOK instruction. Data were collected through a learning interest questionnaire, physical activeness observation sheets, and Strava activity logs, then analyzed using independent t-test or ANCOVA with Cohen’s d effect size calculation. This study is expected to provide empirical evidence regarding the effectiveness of digital technology integration in PJOK learning at the vocational school level and serve as a reference for teachers and education policymakers in developing PJOK instruction that is adaptive to the Merdeka Curriculum.